Thermal vibration of composites and sandwich plates using simple higher order shear deformation theory - Singh, S.K.; Chakrabarti, A. (Journal of Structural Engineering, 2024)
Thermal vibration of laminated composite and sandwich plates is studied by using an efficient C⁰ FE model developed based on simple higher order theory. The C⁰ FE model satisfies zero transverse shear stress conditions at plate top and bottom. In this model the first derivatives of transverse displacement have been treated as independent variables to overcome the problem of C¹ continuity associated with the plate theory. In order to avoid stress oscillations observed in the displacement based finite element, the stress field derived from temperature is made consistent with total strain field by using field consistent approach. It is observed that there is no result available in the literature on thermal vibration of the present problems based on FE model. As such many new results are also generated to show the influence of boundary conditions, ply orientations and plate geometry on the natural frequencies of laminated plates under different thermal loading conditions.